The Response of Manicaria saccifera Natural Fabric Reinforced PLA Composites to Impact by Fragment Simulating Projectiles (2017)
This chapter presents the impact behavior of a recently developed green composite material made of Manicaria saccifera natural fabric reinforced Poly-Lactic Acid (PLA). Composite coupons made of PLA and Manicaria saccifera fabric were produced by compression molding using the film stacking method. The composite ballistic limit (V50) was determined by subjecting PLA/Manicaria coupons, of varying lay-ups and thicknesses, to ballistic impact loading using fragment simulating projectiles (FSPs) according to the MIL-STD-662F standard. It was found that coupons with areal densities between 0.2 and 0.3 g/cm2 displayed a V50 between 50 and 70 m/s. Also, it was found that the V50 increased nonlinearly as a function of coupon thickness, but it does not depend on the composite stacking sequence. Finally, the energy absorbed by the material at impact on complete penetrations is uniform and independent of the striking velocity, whereas for partial penetrations increases exponentially.